2018
DOI: 10.7870/cjcmh-2018-009
|View full text |Cite
|
Sign up to set email alerts
|

The TransKidsNL Study: Healthcare and Support Needs of Transgender Children, Youth, and Families on the Island of Newfoundland

Abstract: This investigation examined needs and concerns of transgender youth and their families throughout the island of Newfoundland. Twenty-four youth and 21 parents completed qualitative questionnaires. Both parent and youth participants expressed concern about general practitioners’ lack of knowledge of transgender healthcare. Trans youths’ main concerns included lack of parental support, feelings of dysphoria, the desire to be fully accepted, and safety. Parents’ main concerns included wait times for care, their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 15 publications
1
23
0
5
Order By: Relevance
“…Research, clinical, and media attention on medical care for trans youth has increased rapidly in recent years. A review of research on trans youth seeking medical care reveals several reviews of care models and practices (Edwards-Leeper & Spack, 2012;Khatchadourian, Amed, & Metzger, 2014;Olson, Forbes, & Belzer, 2011), clinical studies of a variety of mental and physical health characteristics of trans youth seeking care (Olson-Kennedy, Okonta, Clark, & Belzer, 2018), mental and physical health outcomes of hormone therapy (De Vries et al, 2014), examinations of health care providers' perspectives and concerns about offering trans youth care (Knight, Shoveller, Carson, & Contreras-Whitney, 2014;Vance, Halpern-Felsher, & Rosenthal, 2015), ethical approaches to the care of transgender youth (Clark, 2017), barriers to care for trans Gridley et al, 2016;Temple Newhook, Benson, Bridger, Crowther, & Sinnott, 2018a) and non-binary (Clark, Veale, Townsend, Frohard-Dourlent, & Saewyc, 2018) youth, and a community-based study of the future perspectives of trans youth and caregivers (Katz-Wise et al, 2017). An emergent body of research also focuses on the experiences of pre-pubescent gender diverse and trans children (Durwood, McLaughlin, & Olson, 2017;Olson, Durwood, DeMeules, & McLaughlin, 2016;Olson & G€ ulg€ oz, 2018;Temple Newhook et al, 2018b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research, clinical, and media attention on medical care for trans youth has increased rapidly in recent years. A review of research on trans youth seeking medical care reveals several reviews of care models and practices (Edwards-Leeper & Spack, 2012;Khatchadourian, Amed, & Metzger, 2014;Olson, Forbes, & Belzer, 2011), clinical studies of a variety of mental and physical health characteristics of trans youth seeking care (Olson-Kennedy, Okonta, Clark, & Belzer, 2018), mental and physical health outcomes of hormone therapy (De Vries et al, 2014), examinations of health care providers' perspectives and concerns about offering trans youth care (Knight, Shoveller, Carson, & Contreras-Whitney, 2014;Vance, Halpern-Felsher, & Rosenthal, 2015), ethical approaches to the care of transgender youth (Clark, 2017), barriers to care for trans Gridley et al, 2016;Temple Newhook, Benson, Bridger, Crowther, & Sinnott, 2018a) and non-binary (Clark, Veale, Townsend, Frohard-Dourlent, & Saewyc, 2018) youth, and a community-based study of the future perspectives of trans youth and caregivers (Katz-Wise et al, 2017). An emergent body of research also focuses on the experiences of pre-pubescent gender diverse and trans children (Durwood, McLaughlin, & Olson, 2017;Olson, Durwood, DeMeules, & McLaughlin, 2016;Olson & G€ ulg€ oz, 2018;Temple Newhook et al, 2018b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiences of such affirming responses have been related to high levels of satisfaction among young people and their families attending paediatric gender clinics (Inwards-Breland et al, 2019;Pullen Sansfaçon et al, 2019;Tollit, Feldman, McKie, & Telfer, 2019). In terms of limitations, research has identified a lack of understanding by healthcare professionals of transgender young people's needs, discrimination, misgendering, and a lack of training about gender diversity (Carlile, 2020;Corliss et al, 2007;Eisenberg, McMorris, Rider, Gower, & Coleman, 2020;Goldenberg et al, 2019;Gridley et al, 2016;Guss et al, 2019;Heard et al, 2018;Strauss et al, 2017;Temple Newhook, Benson, Bridger, Crowther, & Sinnott, 2018). Such lack of understanding on the part of healthcare professionals can lead to transgender young people and their parents foregoing care (Clark, Veale, Greyson, & Saewyc, 2018;Goldenberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given reported associations between religiosity and transphobia, [32][33][34] it is possible that gender-incongruent youth from religious families feel less supported around their gender identities and are more reluctant to disclose gender incongruence. Parental support 13,16,17 and the ways in which a young person's transgender identity impacts their family 35 have been shown to influence the ability of genderincongruent youth to access GAMC. That fewer older than younger youth had a caregiver who helped them access GAMC suggests another factor that could lead to their later presentation to care.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, although a cause-effect relationship has not been established, an association between later presentation to GAMC and worse mental health among genderincongruent youth has been identified. 2 Barriers to GAMC 13,14 as well as the care-seeking experiences [15][16][17] and decision-making processes 18,19 of gender-incongruent youth have been described. However, the important questions of whether genderincongruent youth who present for GAMC at older ages have different care-seeking experiences or face different barriers than youth who present younger have not been addressed.…”
mentioning
confidence: 99%